Preweaning performance of Yankasa sheep under semi-intensive management - Osinowo, O.A.; Abubakar, B.Y.; Olayeme, M.E.; Balogun, R.O.; Onifade, O.S.; Adewuyi, A.A.; Trimmnell, A.R.; Dennar, F.O. (1994)
Preweaning growth traits and weaning rate of Yankasa sheep under a semi-intensive management system with twice-yearly lambings were studied for nine years at Shika, in the subhumid zone of Nigeria. Least squares means for birth weight (BW), 90-day weaning weight (WW), average daily gain to weaning (ADG) and weaning rate (WR) were 2.5± 0.01 kg, 10.87±0.08 kg, 91.86± 0.91 g/day and 77.8±1.0 per cent, respectively. BW, WW and ADG were significantly affected by parity and the lamb's litter size, sex, month and year of birth. WR was significantly affected by parity, litter size, month and year of birth but not by sex of lamb. Preweaning growth performance was generally better in the wet seasons than in the dry seasons while the reverse was true for weaning rate.